INCIDENCIA DE LA INADECUADA APLICACIÓN DE CONTENIDOS DE LA ASIGNATURA DE MATEMATICAS EN LA CALIDAD DE LA FORMACION DEL PERFIL DE LA BACHILLER EN INFORMATICA EN EL INSTITUTO SUPERIOR TECNOLOGICO '' BABAHOYO'', DURANTE EL PERIODO 2009-2010. - NORGE NARANJO TORRES (2010)
INCIDENCE OF THE INADEQUATE APPLICATION OF CONTENTS OF THE MATHEMATICS SUBJECT ON THE QUALITY OF THE TRAINING OF THE BACHELOR'S PROFILE IN COMPUTING AT THE INSTITUTE SUPERIOR TECHNOLOGY ''BABAHOYO'', DURING THE PERIOD 2009-2010.